Quantification through TLC-densitometric analysis, repellency and anticholinesterase activity of the homemade extract of Indian cloves - Affonso, Raphael S; Lima, Josélia A; Lessa, Bruno M; Caetano, João V O; Obara, Marcos T; Nóbrega, Andréa B; Nepovímová, Eugenie; Musilek, Kamil; Kuca, Kamil; Slana, Gláucia B C A; França, Tanos C C (BMC. Biomedical chromatography, 2018)
The rise of the mosquitoes-transmitted diseases, like dengue, zika and chikungunya in Brazil in the last years has increased concerns on protection against mosquitoes bites. However, the prohibitive prices of the commercially available repellents for the majority of the Brazilian population has provoked a search for cheaper solutions, like the use of the homemade ethanolic extract of Indian clove (Syzygium aromaticum L.) as repellent, which has been reported as quite efficient by the local press. In order to verify this, we performed here the quantification of the main components of this extract through high-performance thin-layer chromatography (HPTLC)-densitometry and evaluated its efficiency as a repellent and its acetylcholinesterase (AChE) inhibition capacity. Our results have proved HPTLC-densitometry as an efficient and appropriate method for this quantification and confirmed the repellency activity, as well as its capacity of AChE inhibition.
Keywords: Adult; Cholinesterase Inhibitors; dospělí; repelenty proti hmyzu; limita detekce; Linear Models; eugenol; Insect Repellents; lineární modely; acetylcholinesterasa; denzitometrie; Acetylcholinesterase; cholinesterasové inhibitory; chromatografie na tenké vrstvě; mužské pohlaví; Reproducibility of Results; mladý dospělý; rostlinné extrakty; lidé; Limit of Detection; Eugenol; reprodukovatelnost výsledků; Plant Extracts; chování zvířat; zvířata; Humans; Behavior, Animal; Chromatography, Thin Layer; Aedes; Male; Animals; Young Adult; Densitometry; Syzygium